The Effect of Feelings of Being Watched on Subjective Happiness and Social Preferences: From a Survey Experiment Using Crowdsourcing - GOTO, Akira (Socio-Informatics, 2023)
In this study, to feel someone is watching me is defined as the “feeling of being watched.” Using crowdsourcing, we investigated the effects of feelings of being watched by a first-party, secondparty, third-party, and supernatural entity on social preferences and subjective happiness.The results showed that the intuitive factor positively impacted subjective happiness, as a variable partially mediated by the feeling of being watched by supernatural beings. In contrast, the intuitive factor positively impacted prosociality, as a variable completely mediated by the feeling of being watched by supernatural beings. Therefore, it is clear that the intuitive feelings of being watched by supernatural entities are essential in both cases.These results suggest that subjective happiness and social preferences may differ depending on what is assumed as monitoring subjects and how we recognize them. In particular, they also suggest the need to reconsider the contemporary significance of supernatural beings.